Reticulon-1 and reduced migration toward chemoattractants by macrophages differentiated from the bone marrow of ultraviolet-irradiated and ultraviolet-chimeric mice - McGonigle, T.; Dwyer, A.; Greenland, E.; Scott, N.; Carter, K.; Keane, Kevin; Newsholme, P.; Goodridge, H.; Pixley, F.; Hart, P. (American Association of Immunologists, 2018)
The ability of macrophages to respond to chemoattractants and inflammatory signals is important for their migration to sites of inflammation and immune activity and for host responses to infection. Macrophages differentiated from the bone marrow (BM) of UV-irradiated mice, even after activation with LPS, migrated inefficiently toward CSF-1 and CCL2. When BM cells were harvested from UV-irradiated mice and transplanted into naive mice, the recipient mice (UV-chimeric) had reduced accumulation of elicited monocytes/macrophages in the peritoneal cavity in response to inflammatory thioglycollate or alum. Macrophages differentiating from the BM of UV-chimeric mice also had an inherent reduced ability to migrate toward chemoattractants in vitro, even after LPS activation. Microarray analysis identified reduced reticulon-1 mRNA expressed in macrophages differentiated from the BM of UV-chimeric mice. By using an anti-reticulon-1 Ab, a role for reticulon-1 in macrophage migration toward both CSF-1 and CCL2 was confirmed. Reticulon-1 subcellular localization to the periphery after exposure to CSF-1 for 2.5 min was shown by immunofluorescence microscopy. The proposal that reduced reticulon-1 is responsible for the poor inherent ability of macrophages to respond to chemokine gradients was supported by Western blotting. In summary, skin exposure to erythemal UV radiation can modulate macrophage progenitors in the BM such that their differentiated progeny respond inefficiently to signals to accumulate at sites of inflammation and immunity.